CRISPR-Cas10-Assisted Structural Modification of Staphylococcal Kayvirus for Imaging and Biosensing Applications - Šimečková, Hana; Bárdy, Pavol; Kuntová, Lucie; Macháčová, Eliška; Botka, Tibor; Bíňovský, Ján; Houser, Josef; Farka, Zdeněk; Plevka, Pavel; Pantůček, Roman; Mašlaňová, Ivana (ACS synthetic biology, 2025)
Recent advances in genome editing techniques based on CRISPR-Cas have opened up new possibilities in bacteriophage engineering and, thus, enabled key developments in medicine, nanotechnology, and synthetic biology. Although staphylococcal phage genomes have already been edited, the modification of their structural proteins has not yet been reported. Here, the structure of Staphylococcus phage 812h1 of the Kayvirus genus was modified by inserting a poly histidine tag into an exposed loop of the tail sheath protein. A two-strain editing strategy was applied, utilizing homologous recombination followed by CRISPR-Cas10-assisted counter-selection of the recombinant phages. The His-tagged phage particles can be recognized by specific antibodies, enabling the modified bacteriophages to be employed in numerous techniques. The attachment of the engineered phage to bacteria was visualized by fluorescence microscopy, and its functionality was confirmed using biolayer interferometry biosensing, enzyme-linked immunosorbent assay, and flow cytometry, demonstrating that the genetic modification did not impair its biological activity.
Keywords: Staphylococcus; editace genu; Gene Editing; CRISPR-Cas systémy; biosenzitivní techniky; Herelleviridae; Biosensing Techniques; stafylokokové bakteriofágy; CRISPR-Cas Systems; Bacteriophage; Poly histidine Tag; CRISPR-Cas10; Staphylococcus aureus; Staphylococcus Phages